Effect of Oral Supplementation with L-Carnitine on Performance Time in a 5000 m Race and Responses of Free Fatty Acid and Carnitine Concentrations in Trained-Endurance Athletes - Mohammad Fayiz AbuMoh'd; Ghaid Obeidat; Walid Alsababha (Montenegrin Sports Academy, 2021)
This study was designed to determine the effect of oral supplementation with L-carnitine on the performance time in a 5000 m race. In addition, free fatty acid, blood carnitine, lactate, and glucose responses to the race following the supplementation period were measured. Twenty male trained-endurance athletes were randomly divided into two groups (L-carnitine, n = 10 (22.13 ± 2.66 yrs) or placebo, n = 10 (21.63 ± 2.23 yrs)). The study was performed with a randomized, double-blind, placebo-controlled parallel-group, in which participants ingested an L-carnitine supplement or a placebo 2 × 1.5 g/day for 3 weeks. Athletes completed a 5000 m race before and after the supplementation period. Blood samples were collected from each athlete before and after the race, preand post-supplementation to measure the physiological responses. Data showed that there were no differences in performance time before (p=0.624) and after (p=0.407) supplementation period between groups and within a group (p>0.05). No differences existed in physiological responses between groups after supplementation before beginning the race (p>0.05), except for the blood carnitine level, which was significantly higher in the L-carnitine than the placebo (P=0.001) group. After the finish of the race, however, data showed better physiological responses in response to L-carnitine supplementation compared to the placebo group (p<0.05). In conclusion, although L-carnitine supplementation increases blood carnitine concentration, it has no beneficial effect on performance time of 5000 m race probably due to the short duration of the race; it might also have no ergogenic effect.